2001
DOI: 10.1007/bf02491608
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of high-resolution gas chromatography and high-performance liquid chromatography for simultaneous determination of lamotrigine and carbamazepine in plasma

Abstract: Key WordsColumn liquid chromatography Gas ch romatog ra phy Lamotrigine Carbamazepine Human plasma SummaryRapid, simple ancl sensitive methods have been devised for simultaneous determination of Jamotrigine (LTG) and carbamazepine (CBZ) in microsamples of human plasma by high-performance liquid chromatography (HPLC) and high resolution gas chromatography (HRGC); both methods have been validated and compared.The HPLC method was more sensitive than HRGC for both drugs, LTG and CBZ. The lowest quantitation limits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Few studies can be found in the literature regarding the determination of LMT as a single analyte or together with other drugs or its metabolites in biological fluids by means of HPLC with UV (or diode array) [107,[185][186][187][188][189][190][191][192][193][194][195], or mass spectrometry [196][197][198] detection and by means of gaschromatography (GC) [199][200][201] or capillary electrophoresis (CE) methods [202][203][204][205]. Only a few papers describe the determination of LMT and its metabolites in biological fluids by means of HPLC with DAD detection [195], electrokinetic chromatography (MEKC) [205], Automated Sequential Trace Enrichment of Dialysates HPLC [206] and HPLC mass spectrometry [196].…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Few studies can be found in the literature regarding the determination of LMT as a single analyte or together with other drugs or its metabolites in biological fluids by means of HPLC with UV (or diode array) [107,[185][186][187][188][189][190][191][192][193][194][195], or mass spectrometry [196][197][198] detection and by means of gaschromatography (GC) [199][200][201] or capillary electrophoresis (CE) methods [202][203][204][205]. Only a few papers describe the determination of LMT and its metabolites in biological fluids by means of HPLC with DAD detection [195], electrokinetic chromatography (MEKC) [205], Automated Sequential Trace Enrichment of Dialysates HPLC [206] and HPLC mass spectrometry [196].…”
Section: Methods Of Analysismentioning
confidence: 99%
“…A literature review revealed that different methods have been reported for the determination of CBZ. These include spectrophotometry , photoinduced fluorimetry , voltammetry , high‐performance liquid chromatography , spectrofluorimetry , micellar electrokinetic capillary chromatography , solid‐phase extraction , chemiluminescence , liquid chromatography , ion chromatography and gas chromatographic methods .…”
Section: Introductionmentioning
confidence: 99%
“…These include HPLC [4][5][6][7][8][9], GC [10][11][12], GC-MS [13,14], radioimmunoassay [15], electrospray ionization-mass spectrometry (ESI-MS) [16], capillary electrophoresis [17][18][19], etc. Unlike HPTLC, all reported methods are cumbersome, time consuming and costlier techniques for estimation of drug in biological samples.…”
Section: Introductionmentioning
confidence: 99%